DE LA REPARATION DES VICTIMES DE LA GUERRE DE SIX JOURS A KISANGANI - KOLUWA, Samy KATUSI (IJRDO - Journal of Social Science and Humanities Research, 2020)
The Democratic Republic of Congo has been a victim of the violation of its sovereignty by Uganda and Rwanda, which their armies known as the Rwandan Patriotic Army and the Ugandan Popular Defense Forces, clashed in the city of Kisangani from June 5 to 10, 2000, causing enormous damage. Only the Republic of Uganda was condemned by the International Court of Justice "I.C.J." to repair the damage caused to the DRC, while Security Council Resolution 1304 condemned them all and also asked them to make reparation. This is so because Rwanda does not recognize the jurisdiction of the I.C.J., although the facts remain real.  It has been nineteen years since the Court condemned Uganda to make reparations to the DRC, which included the victims of the six-day war in its judgment of December 19, 2005; one wonders why up to these days these victims are not always repaired. Therefore, this article provides a historical reminder of this war while exposing the harm suffered by the DRC and its citizen victims as recognized by the court because of Uganda, and proposes the means of execution by which this reparation could be materialized.